PENDEKATAN AGRIBISNIS DALAM PENGEMBANGAN PERTANIAN LAHAN KERING *) (Kasus Lahan Kering di Kabupaten Buleleng, Bali) - ANTARA, MADE (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 2 Juli 2004)
Agribusiness has been a new discourse in development of agriculture and economics in Indonesia. Implementation of agribusiness concept promise many kind of positive benefit for development of agriculture and economics, so that every agricultural activity and which related to agriculture always use agribusiness approach. Development of dry land in East Bali generally and in Buleleng Regency specially with grant support of European economic community (MEE) also use of agribusiness approach, expected can improve prosperity of the farmers in dry land. Therefore, the target of writing of this paper is to present stages and information approach of agribusiness in development of dry land. From result study and reasoning empirical, so can be told that development of dry land agriculture in east Bali generally and in Buleleng regency specially trough agribusiness approach is a precise and correct steps, because this approach to integrate vertically from upstream activity to downstream and by horizontal among various sectors, so that will be able to create feasible profit for farmers in dry land farming. In effort to realize development of dry land agriculture through agribusiness approach which has potency to increase of farmer’s income and also to eliminate economics gap, need support of political will of government (center, province, and regency) and all of society include Non Governmental Organization (NGO) in Buleleng regency. They can be important actors in its realizing, either through development strategy socialization or also through accompanying of farmer in development of advantage agribusiness and co-operation of agribusiness. In the end of project require to evaluate by independent institution about project impact of European Economic Community grant toward improving of socioeconomic condition of the farmer as target of project with analysis methods of before and after project or with and without project.
Keywords: Agribusiness Approach, Development of Dry Land, Buleleng Regency, European Economic Community Grant